Impact of xylan on field productivity and wood saccharification properties in aspen - Derba-Maceluch, Marta; Sivan, Pramod; Donev, Evgeniy N.; Gandla, Madhavi Latha; Yassin, Zakiya; Vaasan, Rakhesh; Heinonen, Emilia; Andersson, Sanna; Amini, Fariba; Scheepers, Gerhard; Johansson, Ulf; Vilaplana, Francisco J.; et al. (Frontiers in Plant Science, 2023)
Xylan that comprises roughly 25% of hardwood biomass is undesirable in biorefinery applications involving saccharification and fermentation. Efforts to reduce xylan levels have therefore been made in many species, usually resulting in improved saccharification. However, such modified plants have not yet been tested under field conditions. Here we evaluate the field performance of transgenic hybrid aspen lines with reduced xylan levels and assess their usefulness as short-rotation feedstocks for biorefineries. Three types of transgenic lines were tested in four-year field tests with RNAi constructs targeting either Populus GT43 clades B and C (GT43BC) corresponding to Arabidopsis clades IRX9 and IRX14, respectively, involved in xylan backbone biosynthesis, GATL1.1 corresponding to AtGALT1 involved in xylan reducing end sequence biosynthesis, or ASPR1 encoding an atypical aspartate protease. Their productivity, wood quality traits, and saccharification efficiency were analyzed. The only lines differing significantly from the wild type with respect to growth and biotic stress resistance were the ASPR1 lines, whose stems were roughly 10% shorter and narrower and leaves showed increased arthropod damage. GT43BC lines exhibited no growth advantage in the field despite their superior growth in greenhouse experiments. Wood from the ASPR1 and GT43BC lines had slightly reduced density due to thinner cell walls and, in the case of ASPR1, larger cell diameters. The xylan was less extractable by alkali but more hydrolysable by acid, had increased glucuronosylation, and its content was reduced in all three types of transgenic lines. The hemicellulose size distribution in the GALT1.1 and ASPR1 lines was skewed towards higher molecular mass compared to the wild type. These results provide experimental evidence that GATL1.1 functions in xylan biosynthesis and suggest that ASPR1 may regulate this process. In saccharification without pretreatment, lines of all three constructs provided 8-11% higher average glucose yields than wild-type plants. In saccharification with acid pretreatment, the GT43BC construct provided a 10% yield increase on average. The best transgenic lines of each construct are thus predicted to modestly outperform the wild type in terms of glucose yields per hectare. The field evaluation of transgenic xylan-reduced aspen represents an important step towards more productive feedstocks for biorefineries.